2010
DOI: 10.1371/journal.ppat.1001179
|View full text |Cite
|
Sign up to set email alerts
|

The Female Lower Genital Tract Is a Privileged Compartment with IL-10 Producing Dendritic Cells and Poor Th1 Immunity following Chlamydia trachomatis Infection

Abstract: While a primary genital tract infection with C. trachomatis stimulates partial-protection against re-infection, it may also result in severe inflammation and tissue destruction. Here we have dissected whether functional compartments exist in the genital tract that restrict Th1-mediated protective immunity. Apart from the Th1-subset, little is known about the role of other CD4+ T cell subsets in response to a genital tract chlamydial infection. Therefore, we investigated CD4+ T cell subset differentiation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 59 publications
5
53
0
Order By: Relevance
“…The MicroTrak EIA is a measure of Chlamydia LPS following swabbing of the genital tract, and although this does not necessarily represent live EBs, we and others have previously shown this to be a valid method of detection of infection especially at early time points during infection. A direct correlation between EIA findings and colony forming units was reported by us previously [32], demonstrating the validity of the EIA method for detection of a genital tract chlamydial infection.…”
Section: Muridarum Infection and Challenge Protocolssupporting
confidence: 79%
See 1 more Smart Citation
“…The MicroTrak EIA is a measure of Chlamydia LPS following swabbing of the genital tract, and although this does not necessarily represent live EBs, we and others have previously shown this to be a valid method of detection of infection especially at early time points during infection. A direct correlation between EIA findings and colony forming units was reported by us previously [32], demonstrating the validity of the EIA method for detection of a genital tract chlamydial infection.…”
Section: Muridarum Infection and Challenge Protocolssupporting
confidence: 79%
“…However, the absence of T cells in the upper genital tract may be attributed to differences in adhesion molecules expressed in the upper or lower genital tracts, and that lower genital tract DCs specifically imprint lower genital tract homing [31]. Indeed, we have previously shown that the uterus and the lower genital tract are remarkably different in the T-cell response to the same pathogen [32]. Following C. trachomatis infection, the upper genital tract developed strong Th1-dominated immunity, while the lower genital tract responded with primarily Th2-mediated immunity and high levels of IL-10.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, Th1, Th2, and Th17 cells release IL-10 to prevent irreversible tissue destruction, chronic inflammation, and autoimmunity. [37][38][39] In our model, NK1R agonists blocked the CREB1/TORC2 pathway in BMDCs, decreasing Il-10 gene transcription and abrogating IL-10 secretion. Moreover, this IL-10 inhibitory effect of NK1R agonists persisted following the induction of high levels of IL-10 by LPS.…”
Section: Discussionmentioning
confidence: 64%
“…by guest www.bloodjournal.org From Indeed, IL-10 is one of the most potent anti-inflammatory cytokines that contributes to maintain peripheral tolerance and tissue homeostasis in the steady state. [37][38][39] Following Ag inoculation and elicitation of acute inflammation, compensatory release of IL-10 limits excessive tissue damage resulting from soluble mediators and immune effector cells. Accordingly, IL-10 secretion is stimulated in DCs and macrophages by a range of Toll-like receptor ligands.…”
Section: Discussionmentioning
confidence: 99%
“…These same cytokines, however, may also be implicated in disease pathogenesis. For many pathogens, including C. trachomatis, IFN plays an important role in resolution of infection (Marks, Tam et al 2010;Agrawal, Bhengraj et al 2011;Matthews, Wilkinson et al 2011;Ohman, Tiitinen et al 2011;Patel, Stefanidou et al 2011). The role of IFN in chlamydial clearance is complicated by the fact that inflammation can damage host cells and IFN itself can also drive persistence (Beatty, Belanger et al 1994).…”
Section: Introductionmentioning
confidence: 99%